(untitled) (Impetus, 2021)
The article “Variations on the motricity in the body Education” arises from a hermeneutic study in which a theoretical and documentary analysis is made about the motricity in some authors who have been used as examples to the theoretical configuration of contemporary Physical Education. In Le Boulch, it is a significant expression of human behaviour, corporal movement is an action that is directed to a particular meaning and the movement is the development thread. In Cagigal, movement is a corporal activity full of human significance. In Parlebas, human movement is a physical practice and motricity is potentiality. The research also retrieves different educational nuances that motricity has: educating through movement and an education by the movement; educating through sports and educating in movement and pedagogy of motricity behaviours.